(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Communication is a behavior whose product is a stimulus to another behavior, whether verbal or non-verbal. This paper aims to describe the various topographies (forms) of human communication, thereby proposing a taxonomyClassification criteria (taxa) for communication responses were elaborated based on the context of responses, their effective medium, their forms, and their products. The result was the proposition of two context categories, five medium categories, two primary form categories, and 21 secondary, tertiary, or other form categories. This resulted in 29 classification possibilities for the communication-behavior response. We concluded that the proposition is relevant since it encourages scientific debate, facilitating both the communication and study of the subject among the researchers.